2000
DOI: 10.1074/jbc.275.20.15490
|View full text |Cite
|
Sign up to set email alerts
|

Role of Src Kinases in the ADAM-mediated Release of L1 Adhesion Molecule from Human Tumor Cells

Abstract: The ectodomain of certain transmembrane molecules can be released by proteolysis, and the solubilized antigens often exert important biological functions. We demonstrated before that the L1 adhesion molecule is shed from the cell surface. Here we show that L1 release in AR breast carcinoma cells is mediated by a member of the disintegrin metalloproteinase (ADAM) family of proteinases. Up-regulation of L1 shedding by phorbol ester or pervanadate involved distinct mechanisms. Pervanadate induced shedding and rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
156
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(166 citation statements)
references
References 55 publications
9
156
0
Order By: Relevance
“…It has been reported that G protein a subunits, such as G ai , directly stimulate Src activity (60), which can lead to MMP-dependent release of EGFR ligands (61). For example, Src activation has been shown to regulate the ADAM-dependent shedding of the L1 adhesion molecule (62). Moreover, several ADAMs have proline-rich Src-homology (SH3) binding domains in their cytoplasmic tails, which can allow interaction with Src (44).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that G protein a subunits, such as G ai , directly stimulate Src activity (60), which can lead to MMP-dependent release of EGFR ligands (61). For example, Src activation has been shown to regulate the ADAM-dependent shedding of the L1 adhesion molecule (62). Moreover, several ADAMs have proline-rich Src-homology (SH3) binding domains in their cytoplasmic tails, which can allow interaction with Src (44).…”
Section: Discussionmentioning
confidence: 99%
“…Cleavage within this domain by plasmin reduces multimerization and RGD-independent integrin binding (21). The 180-and 50-kDa fragments result from membrane-proximal cleavage of the membrane-spanning 200-and 80-kDa L1 forms, respectively, by a metalloprotease, most likely of the ADAM (a disintegrin and metalloprotease) family (27,28). This cleavage step has been proposed to be required for cell migration (28).…”
mentioning
confidence: 99%
“…The 180-and 50-kDa fragments result from membrane-proximal cleavage of the membrane-spanning 200-and 80-kDa L1 forms, respectively, by a metalloprotease, most likely of the ADAM (a disintegrin and metalloprotease) family (27,28). This cleavage step has been proposed to be required for cell migration (28). Because specific proteolytic processing of L1 is important for regulation of neuronal migration and neurite outgrowth, we have searched for the proteases responsible for cleaving L1 at the two sites and investigated some of the structural and functional consequences of this proteolytic cleavage.…”
mentioning
confidence: 99%
“…In contrast, little is as yet known about natural inducers and signaling pathways that activate ectodomain shedding under physiological conditions. Recent studies (32)(33)(34)(35)(36) have uncovered the roles of mitogen-activated protein (MAP) kinase signaling pathways in the activation of ectodomain shedding. Thus, growth factors and activated tyrosine kinase receptors rapidly induce ectodomain shedding of TGF-␣ and other transmembrane proteins through induction of the Erk MAP kinase signaling pathway without the need for new protein synthesis (32).…”
mentioning
confidence: 99%